P268 Bloodstream infections in paediatric immunocompromised patients, responsible pathogens, antibiotic susceptibility patterns and treatment outcomes: experience of single centre in turkey. (6th June 2017) - Kara, Tuğçe Tural; Özdemir, Halil; Erat, Tuğba; Yahşi, Aysun; Kocabaş, Bilge Aldemir; Aysev, Ahmet Derya; Ileri, Dilber Talia; Ince, Elif; Taçyildiz, Nurdan; Ünal, Emel; Çiftçi, Ergin; Ince, Erdal
Abstract : Background and aims: Bloodstream infections are the major cause of morbidity, increased cost, prolonged hospitalisation and mortality in paediatric haematology and oncology patients. We aimed to identify causative microorganisms and their antimicrobial susceptibilities in paediatric immunocompromised patients. Methods: Patients with haematological and/or oncological diseases who admitted to our hospital with fever between January 2010 and November 2015 were included in this study. Patients' demografic and clinical findings were collected from hospital information systems and microbiology laboratory records retrospectively. Results: Totally 71 paediatric patients who had 111 bloodstream infection episodes were included in this study. The median age of patients was 90 (3-247) months. The most underlying disease was acute lymphoblastic leukaemia. While 31 patients had only peripheral blood culture positivity, 80 patients had catheter related blood stream infections. Of 80.2% blood stream infections occurred in neutropenic period. Responsible pathogens were detected as follows: 35.1% gram-positive microorganisms, 60.5% gram-negative bacteria and 4.4% fungi. The most causative gram negative pathogen was Escherichia coli and the most isolated gram positive microorganism was meticillin resistant coagulase negative Staphylococci. Extended spectrum beta lactamase was produced by 60% of Klebsiella spp. and 42.1% of E. coli. In addition carbapenemase producing E. coli and Klebsiella spp. were 15.8% and 26.7% respectively. Enterococcus spp. had 88.9% ampicillin resistance and%33.3 vancomycin resistance. Bloodstream infection related mortality rate was 2.7%. Conclusion: Gram negative microorganisms were predominant pathogens in bloodstream infections. Extended spectrum beta lactamase and carbapenem resistance were increasingly important and they limited treatment options. The choice of empiric antimicrobial drug in immunosuppressed patients is life-saving. For all these reasons, the choice of empirical antibiotics should be made according to the clinical condition of the patient and the prevalent microorganisms in the current clinic, as favourable antimicrobial therapy will be able to achieve positive clinical outcomes.